Optimizing Agricultural Food Institutions at the Farmer Level to Enhance Rice Productivity: A Strategic Approach for Sustainable Development - Istifadhoh, Emilia; Patiung, Markus; Wisnujati, Nugrahini Susantinah (PT. Sangadji Media Publishing, 2024)
This study aims to analyze the role of agricultural food institutions at the farmer level in enhancing rice productivity in Lamongan Regency, East Java. It examines the contributions of these institutions to productivity and identifies strategies to optimize their functions, thereby improving the overall business environment for farmers. Employing a descriptive research method with a survey design, primary data were collected through structured interviews and direct observations from agricultural extension workers and farmers, complemented by secondary data from relevant publications. The findings indicate that agricultural food institutions play a moderately effective role in boosting rice production, influenced by factors such as land ownership, farmer group participation, access to technology, and market access. Specifically, effective land management and high soil quality positively affect productivity, while appropriate technology and active engagement in farmer groups further enhance yields. However, challenges such as inadequate land management practices, the need for technological innovation, limited farmer participation in group activities, and insufficient market access hinder optimal productivity. This study contributes to understanding the intersection of institutional dynamics and agricultural productivity and offers insights for strengthening agricultural institutions to support sustainable agricultural development. Future research should explore different regions and crops and delve deeper into market dynamics, technological innovations, and policy interventions to enhance farmer welfare and productivity.